Resistência e violência em Horacio Quiroga e Sergio Faraco - Leites, Amalia Cardona (2013)
This paper analyzes four short stories from Uruguayan writer Horacio Quiroga: Los mensú, A la deriva, Una bofetada e Los desterrados and four short stories from Brazilian writer Sergio Faraco: : A voz do coração, Noite de matar um homem, Guapear com frangos e Hombre, adopting the conception of border as a promiscuous place where the transgression is cultivated. The narratives are compared and related in the aspects in which the protagonists identities are constructed, especially in the relationship with their environments. When we discuss the question about the local identities and the borders in Latin America, we locate ourselves and establish our own positioning, also locating the other who is object of the discourse. To recognize the other implies recognizing oneself, and this process, since it is subject to constant transformations, involves to transit in the past and in the present, so the past can also be constructed and better understood. In order to do so, the way chosen is that in which the literary analysis dialogues with the historical contextualization of the spaces where the narratives are located, and also with the concept taken from Geography - of territorialization. To this concept we add the ideas of in-between place. and transculturation (respectively, according to Silviano Santiago and Ángel Rama), cardinals to a better understanding of Latin American literature. The comparison of the eight short-stories is started with the aspect of endurance, in which after the analysis we verified that is manifest in the authoritarian relationship of man against man, where the violence and the economic power are the vehicle of the ruling class oppression. The endurance is also the element that comes out in the conflict between man and nature at isolated and still wild territories, the environmental forces defeat the man and break his original harmony with the place. The ideal of the noble savage who lives in total equilibrium with his environment has no place at Quiroga s and Faraco s America. The nature, in this paper, is directly related to the inhuman realm, to the instincts opposed to the reason, to the expressions of violence not monopolized by the state, to the violence and brutality in its ancestral condition. So, either at the so called civilization or barbarity , the characters identity is formed in the confrontation and in the endurance (yet unfruitful) to the authoritarianism and to the environment. Finally, to think about borders means to bring out different ways of understanding life and different sensitivities. Through comparative analysis, it is possible to come upon different times and spaces and see how they dialogue, resemble and differ from each other. When we approached the short stories of Horacio Quiroga and Sergio Faraco, what was protruded was the condition of cultural and economic misery of the protagonists who, ignoring their condition, became victims of an authoritarian system which is not possible to challenge and, above all, from which is not possible to escape.